2020
DOI: 10.1016/j.jcv.2020.104586
|View full text |Cite
|
Sign up to set email alerts
|

Redondovirus DNA in human respiratory samples

Abstract: Highlights ReDoV infection may not be systemic or the presence of circulating virus can be only intermittent. ReDoV infection is mainly present in the respiratory tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
1
18
1
Order By: Relevance
“…The prevalence (56.9%) of redondoviruses detected in our study participants was higher than the reported prevalence of 15% in the oropharynx of healthy Americans [8], 11% among Italians [10], and 2% among Spanish subjects [11]. However, phylogenetic analysis found no large-scale geographical clustering between viruses detected in Vietnam, the US, Spain, and China, indicating the wide geographic distribution and genetic diversity of redondoviruses.…”
Section: Discussioncontrasting
confidence: 83%
“…The prevalence (56.9%) of redondoviruses detected in our study participants was higher than the reported prevalence of 15% in the oropharynx of healthy Americans [8], 11% among Italians [10], and 2% among Spanish subjects [11]. However, phylogenetic analysis found no large-scale geographical clustering between viruses detected in Vietnam, the US, Spain, and China, indicating the wide geographic distribution and genetic diversity of redondoviruses.…”
Section: Discussioncontrasting
confidence: 83%
“…Anelloviridae levels are typically elevated in immunocompromised states ( 13 , 14 ). Redondoviridae are a recently-described family of viruses that appear restricted to the human oral and respiratory tract and have a prevalence of up to 15% ( 15 , 33 ). Redondoviridae levels are elevated in the airway of intubated patients and in oral samples of periodontitis patients ( 15 , 33 ), suggesting that they may be barometers for disease activity in some conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As with Anelloviridae , whether Redondoviridae can cause disease is unknown. Preliminary studies show increased levels of redondoviruses in humans with periodontitis, patients who are critically ill in a medical intensive care unit and individuals with severe respiratory diseases 32 , 33 , although to date there is no evidence that redondoviruses are contributing to the disease states. Thus, both anelloviruses and redondoviruses appear to be common commensal viruses that might be undetected if not for developments in viral metagenomic sequencing methods.…”
Section: Virome Of Different Body Sitesmentioning
confidence: 99%
“…Greater abundance of Anelloviridae has been found in indi viduals who are immunocompromised, including the recipients of lung transplants, individuals who are HIV positive and individuals on immuno suppressive medi cations owing to inflammatory bowel disease, indicat ing that Anelloviridae are normally under host immune control 12,14,[29][30][31] . The newly discovered Redondoviridae are another family of small circular DNA viruses that appear to be widespread commensals commonly found in the respiratory tract [32][33][34] .…”
Section: Human Virome Diversitymentioning
confidence: 99%
See 1 more Smart Citation